Circulating ICAM-1 and VCAM-1 in Peripheral Artery Disease and Hypercholesterolaemia: Relationship to the Location of Atherosclerotic Disease, Smoking, and in the Prediction of Adverse Events - Blann, Andrew D.; Seigneur, Martine; Steiner, Michael; Miller, J. Paul; McCollum, Charles N. (Thrombosis and Haemostasis, 1998)
We examined the relationship of soluble intercellular adhesion molecule-1 (sICAM-1) and vascular cell adhesion molecule-1 (sVCAM-1) with smoking and hypercholesterolaemia in peripheral artery disease (PAD). Serum samples were obtained from 119 patients with objectively-proven PAD, 39 patients with hypercholesterolaemia but asymptomatic for PAD, and 132 age and sex matched asymptomatic controls. Using ELISAs, we found increased sICAM-1 and sVCAM-1 (both p <0.01) in the patients with PAD relative to the controls, but no significant change in patients with hypercholesterolaemia. However, the effect for sVCAM-1 was lost when smoking was entered as a covariate. Only sICAM-1 was higher in patients with PAD in the femoral/iliac arteries compared to the carotid arteries (p <0.05). In a 39-month follow-up of 112 patients with PAD, increased ICAM-1 weakly (univariate p <0.05) predicted those 57 whose disease progressed (i.e. to end points such as myocardial infarction and arterial surgery). However, high fibrinogen was a much better (univariate p = 0.001, multivariate p <0.05) predictor of disease progression. We suggest (i) that increased levels of sVCAM-1 in atherosclerosis are due to smoking, (ii) that increased sICAM-1 is independent of this risk factor, (iii) that both these changes are independent of hypercholesterolaemia, and (iv) that increased sICAM-1 is a weak predictor of disease progression in peripheral atherosclerosis.